The science fiction horror: Alien, George R. R. Martin's Nightflyers and the surveillance of women. (1st November 2019) - Marotta, Melanie A.
AbstractThe subgenre of the science fiction horror has a lengthy history, one that is purported to begin with Mary Shelley's novel, Frankenstein (1818). In Shelley's novel, the body is a space in which a man enacts his ambitions. Significantly, the female voice that was so prominent in the novel disappears in later adaptations including Danny Boyle's National Theatre production examined here. In the science fiction horror film of the later twentieth century, the monstrosity appears famously in what is now a franchise. Ridley Scott directs Alien (1979), a renowned haunted ship mystery (territory of the horrific). When she is not defending herself from attacks, Ripley must contend with her objectification by Ash, the corporation's representative and by the rest of the crew. A new addition to the science fiction horror subgenre is Syfy channel's adaptation of George R. R. Martin's Nightflyers. Unbeknownst to the crew of the Nightflyer, the former captain of the ship, Cynthia, has had her consciousness transferred to the ship and she is watching everyone. Like Ripley, the Nightflyer's female characters ‐ Agatha, Melantha and Cynthia ‐ are subjected to others' fear of the unknown, namely the changing roles for women and how that will impact their societal construction. Here, I will examine the body on display. This essay is primarily interested in the female characters and whether or not they are empowered or violated by the act of looking or violated.